Effects of digitalization on the human centricity of social security administration and services - Brian Lee-Archer (International Labour Organization (ILO), 2023)
Human-centered social security administrations keep the human dimension in control of decision-making. This is made possible through the insight to be gained from digital data-driven innovation in policy and governance and managerial reforms. Moreover, there are risks associated with collecting and analysing people's digital data analysed and using it to further automate business processes. Human centricity is examined in this paper, through a human + machine approach, starting with social policy through to service delivery. Machines using AI and related technologies are designed to aug¬ment rather than replace human decision-making capability. This augmentation approach is essential in matters where discretion, compassion, reasoning, judgement, and empathy are essential for equity, fair¬ness, and fiscal responsibility within social security administration. This working paper presents a series of vignette style case studies (13) as examples of digitisation and/or digitalisation in the context of human centricity in social security administration.
Keywords: 330; social security administration; technology